Korean autistic persons facing systemic stigmatization from middle education schools: daily survival on the edge as a puppet - Yoon, Wn-ho; Seo, JaeKyung; Je, Cheolung (Frontiers in Psychiatry, 2024)
Introduction Korean autistic persons who have endured an integrated secondary education system have been exposed to school bullying, causing trauma and stigma to them. It also blocks them from entering a tertiary education system and a decent work, resulting in a lower quality of life. However, research on how it affects autistic persons has not yet been conducted in Korea. Methods Fourteen adult autistic persons in the Republic of Korea participated in the semi-structured focused group interviews. Their conversations were analyzed through qualitative coding. Results The interview results show the rare voice of Korean autistic people. Although interviewees experienced physical, verbal, and sexual violence against them during the secondary education period, they could not get substantial assistance from schools and society. Interviewees agreed that bullying is inherent in the secondary education system of Korea, even in Korean culture. They experienced the cause of bullying being attributed to them as victims rather than perpetrators, and impunity is given to the bullying assailants. Early analyses of this article confirm that such experiences are combined with the sociocultural climate of elitism, meritocracy, and authoritarianism in the Republic of Korea. Conclusion The study confirmed that the autistic person’s bullying experience does not come from the social inability of autistic people but the “profound” competition and discriminative atmosphere of the society. The result urges further studies on the bullying experience of East Asian autistic persons and the construction of Korean intervention strategies to prevent school violence against Koreans with disabilities, especially autistic pupils.